Optimasi Formula Foot Spray Gel Minyak Atsiri Bunga Lavender Dengan Variasi Konsentrasi Carbopol 940 Sebagai Gelling Agent - Nurul Fitri Dirgahayu Yahya; Muhammad Asri SR; Nurqalbi SR; Suryanita (Jurusan Farmasi Poltekkes kemenkes Makassar, 2025)
ABSTRACT Foot odor is a prevalent issue resulting from excessive perspiration and bacterial proliferation in moist environments. This research aimed to optimize the formulation of a lavender (Lavandula angustifolia Miller.) essential oil foot spray gel by varying the concentration of Carbopol 940 as a gelling agent. In this laboratory-based experimental study, three formulations were developed containing 0.3%, 0.5%, and 0.7% Carbopol 940. Evaluations involved organoleptic assessment, homogeneity, pH measurement, viscosity testing, spreadability, adhesion, and stability evaluation through cycling tests. All formulations fell within the skin’s pH range (4.5–6.5) and demonstrated good homogeneity. Findings indicated that higher Carbopol 940 concentrations increased viscosity while reducing spreadability. The 0.5% Carbopol 940 formulation provided the optimal balance between viscosity, spreadability, and physical stability. Cycling test results confirmed that this formulation remained stable without notable changes in physical characteristics. It is concluded that the optimal lavender essential oil foot spray gel formulation was achieved at a Carbopol 940 concentration of 0.5%. Keywords: Carbopol 940, foot spray gel, lavender, essential oil